Contextual Effect of School on Nutrition Intake to Prevent Anemia Among Female Adolescents in Yogyakarta - Cynara, Ailsa Clarissa; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Inadequate nutritional intake can affect the body condition of young women, one of effects is increasing the incidence of anemia. The Health Belief Model theory can determine how a person will behave in deter